Assessing the importance of treatment goals in patients with psoriasis: analytic hierarchy process vs. likert scales - Gutknecht, Mandy; Schaarschmidt, Marthe-Lisa (The Patient, 2018)
To define treatment benefit, the Patient Benefit Index contains a weighting of patient-relevant treatment goals using the Patient Needs Questionnaire, which includes a 5-point Likert scale ranging from 0 (“not important at all”) to 4 (“very important”). These treatment goals have been assigned to five health dimensions. The importance of each dimension can be derived by averaging the importance ratings on the Likert scales of associated treatment goals.
Gesehen am 21.12.2020